Children’s play and participation in preschool activities: Stuðningur deildarstjóra og annars starfsfólks - Hreinsdóttir, Anna Magnea; Pálsdóttir, Pála; Grétarsdóttir, Sigrún (Menntavísindasvið Háskóla Íslands, 2024)
The aim of this study was to shed light on how the heads of departments in four preschools, which participated in a collaborative study, which supported play as the main means of learning for children and children’s participation in daily activities. The purpose was to identify support and effective methods that strengthen play as the main method of learning for children to increase children’s active participation in the day-today work of preschools. The following questions guided the research: How do the heads of departments support children’s play in the preschools? How do the heads of departments promote the active participation of children in their daily work? How is knowledge of play and children’s participation shared with colleagues? Four preschools in Reykjavík, Engjaborg, Funaborg, Hólaborg and Sunnufold participated in a two-year project to support children’s play and their participation in the day-to-day work of the preschools. The project was part of the implementation of the Education Policy of the City of Reykjavík, which has supported the project. A researcher at the University of Iceland has advised the project. The department heads at the preschools met regularly to learn about and discuss various ways to support children’s play and increase their participation in the preschools’ work. The Icelandic National Curriculum (Mennta- og menningarmálaráðuneyti, 2012) has adopted a rights-based approach that views children as capable, active preschool participants with opinions that can be communicated if listened to. Play is children’s most important means of learning, and the role of adults is key when considering learning through play and how to support the development of play (Wood, 2013). Peer culture and the children’s group are also important because children learn from each other (Corsaro, 2015). The United Nations Convention on the Rights of the Child (1989) recognises children as individuals and agents of social change. The Convention sets out the need to listen to children and enable their ...